Pelatihan Kewirausahaan dan Komunikasi Pemasaran pada UMKM sebagai Bagian dari sektor Pariwisata di Lingkungan PKK Desa Sukaraharja - Rakista, Putri; Nurkarim, Syamsu; Karismatika, Anggi Permata (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
Entrepreneurship and Marketing Communication Training for UMKM in the PKK Environment of Sukaharja Village Micro businesses are business activities that are able to expand employment opportunities and provide broad economic services to the community. UKM business development is generally directed at overcoming poverty and inequality in society as well as creating job opportunities and increasing exports, invigorating agricultural and rural businesses. This entrepreneurship training aims to provide understanding and understanding in the field of entrepreneurship with various kinds of material, including: growing business ideas, solving problems in starting a business, increasing motivation and self-confidence in starting an UMKM business. Suraharja Village is an area that has UMKM potential. This activity was initiated by the PKK women's organization. However, in its implementation, business implementation in Sukaraharja Village still encountered obstacles such as minimal variety in business types so that marketing was stagnant. Thus, to further increase the variety of business types of UMKM in Sukaharja Village, we must be able to observe and analyze business potential that can be developed in the village and is needed through instilling an entrepreneurial spirit in UMKM players.